5th Annual Vancouver Folk Music Festival - Vancouver Folk Music Festival Societyet al (1982)
Jericho Beach Park 5TH ANNUAL Vancouver Folk Music Festival/ - A Capella [sic] - African - Bluegrass - Blues - Caribbean - Cajun - Country - Fancy Pickin' - Feminist - Irish - Jazz - Jewish - Mexican - Native North American - Newfoundland - Old Timey - Quebecois - Scottish - Songwriters - Swedish - Swing - Tex-Mex - Vaudeville - Welsh -/ July 16, 17, 18, 1982 Jericho Beach Park -Main Stage Concerts Each Evening -5 daytime Workshop Stages Sat. & Sun. -Crafts -Children's Programming -Food/ Here's who's coming: Odo Addy & Kukrudu - Ar Log - Eddie Belchowski Tony Bird & Morris Goldberg - The Bluegrass Band Eric Bogle with John Munro - Roy Bookbinder La Bottine Souriante - Boys of the Lough Bright Morning Star - Chautauqua '82 Meg Christian - Beverly Cotton Darcie Deaville - John Fahey John Faulkner, Dolores Keane & Reel Union Ferron - Cathy Fink - The Robin Flower Band Don Freed - Gayap Rhythm Drummers The Harmony Sisters - The Hunt Family Santiago Jimenez, Jr. y su conjunto norteno Bengt Jonsson, Gunna Ostergards & Thomas Westling Monique Jutras & Gilles Losier The Katari Taiko Group - Koerner, Ray & Glover Eli Lahav - Alain Lamontagne & Esther Larose Don Lange - Country Joe McDonald Dougie McLean - John McCutcheon - Rose Maddox Charlie Maguire - Geof Morgan Holly Near with Ronnie Gilbert & Adrienne Torf New Prairie Ramblers - Norrlatar - U. Utah Phillips Queen Ida's Bon Temps Zydeco Band Chris Rawlings - Red Clay Ramblers - Stan Rogers Betsy Rose & Cathy Winter Kelly Russell, Rufus Guinchard & Jim Payne Saheeb - Marc Savoy, Anne Savoy & Mike Doucette Claudia Schmidt - David Sereda Silly Wizard - Alan Stivell - Stringband Themba Tana - Los Trovadores de la Costa Valdy - Peter Paul Van Camp - Dave Van Ronk Townes Van Zandt - Robin & Linda Williams Cris Williamson - Takeo Yamashiro/ Glen E Erikson Graphics/ Sponsored by the Vancouver Folk Music Festival Society with assistance from the City of Vancouver; Vancouver Board of Parks & Recreation; The Heritage Festival Society; the Province of British Columbia Cultural Services Branch; International Year of Disabled Persons, B.C. Committee; and the Department of Employment & Immigration./ With the assistance of the TOURING OFFICE of the Canada Council/ Admission prices: Early Bird Special (before June 19) .00 Advance Weekend Tickets (after June 19) .00 Weekend Tickets at the Gate .00 Friday night .00 Saturday & Sunday ea. .00 Children under 12 accompanied by adult, and O.A.P. FREE/ Tickets available in Vancouver at Vancouver Ticket Centre Outlets and all Eaton's stores (687-1818); at Black Swan Records 2936 W. 4th (734-2828), and Octopus Books, 1146 Commercial Dr. (253-0931); in Victoria at Richards Records, 1318 Government St. (383-2733) and Victoria Folklore Centre, 539 Pandora Ave. (383-3412). Further information and tickets including mail orders from Vancouver Folk Music Festival, 3271 Main Street, Vancouver, B.C., V5V 3M6 Telephone (604) 879-2931